Probable Mechanisms of Needling Therapies for Myofascial Pain Control - Chou, Li-Wei (Hindawi Publishing Corporation, 2012)
Myofascial pain syndrome (MPS) has been defined as a regional pain syndrome characterized by muscle pain caused by myofascial trigger points (MTrPs) clinically. MTrP is defined as the hyperirritable spot in a palpable taut band of skeletal muscle fibers. Appropriate treatment to MTrPs can effectively relieve the clinical pain of MPS. Needling therapies, such as MTrP injection, dry needling, or acupuncture (AcP) can effectively eliminate pain immediately. AcP is probably the first reported technique in treating MPS patients with dry needling based on the Traditional Chinese Medicine (TCM) theory. The possible mechanism of AcP analgesia were studied and published in recent decades. The analgesic effect of AcP is hypothesized to be related to immune, hormonal, and nervous systems. Compared to slow-acting hormonal system, nervous system acts in a faster manner. Given these complexities, AcP analgesia cannot be explained by any single mechanism. There are several principles for selection of acupoints based on the TCM principles: “Ah-Shi” point, proximal or remote acupoints on the meridian, and extra-meridian acupoints. Correlations between acupoints and MTrPs are discussed. Some clinical and animal studies of remote AcP for MTrPs and the possible mechanisms of remote effectiveness are reviewed and discussed.